2013
DOI: 10.1111/1556-4029.12203
|View full text |Cite
|
Sign up to set email alerts
|

Expertise in Fingerprint Identification

Abstract: Little is known about the nature and development of fingerprint expertise and, therefore, the best way to turn novices into experts. Little is known about the factors that affect matching accuracy and, therefore, what experts can legitimately testify to in court. This thesis explores the factors that affect matching accuracy and the development of expertise in fingerprint identification, in order to inform training, and to provide an empirical basis for expert testimony in the courtroom. The investigation is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 103 publications
(224 reference statements)
4
66
1
Order By: Relevance
“…Examiners are highly accurate when they individualize [2][3], but they do not always agree whether the evidence supports individualization, as opposed to exclusion (different sources) or inconclusive [2], [4][5]. There are two aspects to the sufficiency criteria: the examiner's assessment of the content of the prints, and how much agreement is sufficient (given the clarity, distortion, and the rarity of the configurations of the features); neither is standardized.…”
Section: Introductionmentioning
confidence: 99%
“…Examiners are highly accurate when they individualize [2][3], but they do not always agree whether the evidence supports individualization, as opposed to exclusion (different sources) or inconclusive [2], [4][5]. There are two aspects to the sufficiency criteria: the examiner's assessment of the content of the prints, and how much agreement is sufficient (given the clarity, distortion, and the rarity of the configurations of the features); neither is standardized.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of prints have been identified but no two fingers give the similarity on each other even from two fingers of the same individual (Alaa Ahmed Abbood, Ghazali Sulong & Peters, 2014; Matthew B. Thompson, 2013;Sharma, 1989;Urbach, 1989). Series of experiments conducted to describe on the effect of superimposition techniques for fingerprints prove that with the best superimposed techniques, even from the same finger, the similarities could not be produced due to imperfect inking, unbalanced pressure, the texture of surface of paper and several other aspects (Bernard Roberston, 1995;Bradford T. Ulery, 2011;Sharma, 1989).…”
Section: Law Of Individuality and Locard's Principlementioning
confidence: 99%
“…These fingerprint examiners have testified in court for over one hundred years, but there have been few experiments directly investigating the extent to which experts can correctly match fingerprints to one another, how competent and proficient fingerprint experts are, how examiners make their decisions, or the factors that affect performance (Loftus and Cole, 2004; Saks and Koehler, 2005; Vokey et al, 2009; Spinney, 2010b; Thompson et al, 2013a). Indeed, many examiners have even claimed that fingerprint identification is infallible (Federal Bureau of Investigation, 1984).…”
mentioning
confidence: 99%
“…A similar experiment, with participants from the US Federal Bureau of Investigation, produced similar results (Ulery et al, 2011), and a follow-up experiment found variability in the consistency within and between examiners' decisions (Ulery et al, 2012). An examiner's expertise seems to lie, not in matching prints per se , but in discriminating highly similar but nonmatching prints (Thompson et al, 2013a). …”
mentioning
confidence: 99%